THE EFFECT OF CR ON THE SOLUBILITY OF AL IN ORTHOPYROXENE: EXPERIMENTS AND THERMODYNAMIC MODELLING - Klemme S.; StC O'Neill H. (My University, 2000)
The partitioning of chromium and aluminium between coexisting orthopyroxene and spinel in equilibrium with forsterite in the system MgO-Al2O3-SiO2-Cr2O3 (MAS-Cr) has been experimentally determined as a function of temperature, pressure and Cr/(Cr + Al) ratio. Experiments were conducted at temperatures between 1300 and 1500 °C and at pressures from 5 to 54 kbar. Previous experimental results on the (Al, Cr)2O3 and Mg(Al, Cr)2O4 solid solutions have been combined with the present results plus relevant data from the CMAS system to derive a thermodynamic model for Al-Cr-bearing orthopyroxenes, spinels and corundum-eskolaite solid solutions. The orthopyroxene solid solution can be modelled within the accuracy of all experimental constraints as a ternary solid solution involving the components Mg2Si2O6 ( E), MgAl2SiO6 (M) and MgCr2SiO6 (C), in which the activities are related to composition through the equations: The mole fractions are defined as where nAl and nCr are the number of Al and Cr cations per orthopyroxene formula unit of six oxygens. These expressions reduce to one-site mixing for Mg2Si2O6-MgAl2SiO6 orthopyroxenes in the Cr-free system, but are equivalent to two-site mixing for the exchange of Al and Cr between orthopyroxene and spinel, as required by the experimental data. We find WopxEM=WopxEC = 20 kJ mol-1 and WopxMC=0.